AN ANALYSIS OF OPPORTUNITY AND CHALLENGE OF DAYCARE INDUSTRIES IN MAKASSAR CITY - Ganap, Adella Bellatrix Zephaniah; Thelessy, Ira; Fidianti, Findaria Nur; Tanzil , Gabriel Enrico; Sharon, Salmah; Firman, Afrizal (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
The daycare industry in Makassar has shown significant growth recently, driven by the increasing number of dual-income households and changing patterns of early childhood care. This study explores the opportunities and challenges faced by daycare businesses inthe city, focusing on operational, social, and market-related aspects. Opportunities include the rising awareness among parents regarding early childhood education, growing demand for flexible childcare services, and potential partnerships with corporations,healthcare providers, and educational institutions. Additionally, the relatively limited number of high-quality daycare centers in suburban areas offers room for expansion. However, several challenges persist, such as high operational costs, a shortage of trained caregivers, cultural preferences for family-based childcare, and competition from informal providers offering lower prices. The study highlights the importance of adopting innovative solutions, including technology-enabled monitoring systems, diversified service packages, and continuous staff development programs to enhance service quality and build customer trust. By addressing these challenges and leveraging the available opportunities, daycare businesses in Makassar can achieve sustainable growth and contribute to improving early childhood care standards in the region. This research offers helpful tips for entrepreneurs, policymakers, and stakeholders in developing strategies to strengthen the competitiveness of the daycare sector.